What is the optimal dose of botulinum toxin A in the treatment of cervical dystonia? Results of a double blind, placebo controlled, dose ranging study using Dysport®. Issue 1 (1st January 1998) - Poewe, W; Deuschl, G; Nebe, A; Feifel, E; Wissel, J; Benecke, R; Kessler, K R; Ceballos-Baumann, A O; Ohly, A; Oertel, W; Künig, G
Abstract : OBJECTIVES: Botulinum toxin injections have become a first line therapeutic approach in cervical dystonia. Nevertheless, published dosing schedules, responder rates, and frequency of adverse events vary widely. The present prospective multicentre placebo controlled double blind dose ranging study was performed in a homogenous group of previously untreated patients with rotational torticollis to obtain objective data on dose-response relations. METHODS: Seventy five patients were randomly assigned to receive treatment with placebo or total doses of 250, 500, and 1000 Dysport® units divided between one splenius capitis (0, 175, 350, 700 units) and the contralateral sternocleidomastoid (0, 75, 150, 300 units) muscle. Assessments were obtained at baseline and weeks 2, 4, and 8 after treatment and comprised a modified Tsui scale, a four point pain scale, a checklist of adverse events, global assessment of improvement, and a global rating taking into account efficacy and adverse events. At week 8 the need for retreatment was assessed and then the code was unblinded. For those still responding, there was an open follow up until retreatment to assess the duration of effect. RESULTS: seventy nine per cent reported subjective improvement at one or more follow up visits. Decreases in the modified Tsui score were significant at week 4 for the 500 and 1000 unit groups versus placebo (p<0.05). Additionally positive dose-response relations were found for the degree of subjective improvement, duration of improvement, improvement on clinical global rating, and need for reinjection at eight weeks. A significant dose relation was also established for the number of adverse events overall and for the incidence of neck muscle weakness and voice changes. CONCLUSION: Magnitude and duration of improvement was greatest after injections of 1000 units Dysport®; however, at the cost of significantly more adverse events. Therefore a lower starting dose of 500 units Dysport® is recommended in patients with cervical dystonia, with upward titration at subsequent injection sessions if clinically necessary.